Sustainable Development Goals (SDGs) as Convergence in Inclusive Spatial Planning Policy - Giftian Fajri Rustyono; Batara Wahyu Putera; Nanda Dwi Purnama; Bobo Alex Sandro; Arlangga Surya Renata (Universitas Muhammadiyah Surakarta, 2024)
As a global agenda, Sustainable Development Goals (SDGs) serve as a guideline for all international countries in implementing development with accountability for the well-being of both humans and the environment. From this foundation, the reasons why Sustainable Development Goals are important lie in their integration of economic, social, and environmental dimensions in development. Therefore, when examining these goals and connecting them to spatial policies, harmony is generated. This research demonstrates that the convergence between SDGs and Spatial Planning Policies has a significant impact on sustainable development, considering that spatial planning itself aligns various aspects of development. This ensures that land and space utilization can be maximized and optimized efficiently without sacrificing much. By integrating SDGs into Spatial Planning Policies, a more inclusive spatial plan can be created.